Carbon quantum dots: synthesis, properties, and sensing applications as a potential clinical analytical method. Issue 17 (12th April 2019) - Huang, Saipeng; Li, Wenshuai; Han, Pu; Zhou, Xin; Cheng, Jiewei; Wen, Huiyun; Xue, Weiming
Abstract : Carbon quantum dots (CDs) are a novel class of fluorescent carbon nanoparticles and nanomaterials with fascinating properties, which have attracted worldwide attention and have been applied in different fields during the last decade. Abstract : Carbon quantum dots (CDs) are a novel class of fluorescent carbon nanoparticles and nanomaterials with fascinating properties, which have attracted worldwide attention and have been applied in different fields during the last decade. In this article, we have reviewed the recent progresses made in the field of bioanalysis and biosensor, focusing on their synthesis methods, use of novel precursors, particle size control, construction methodologies and modification strategies, quantum yields, photoluminescence properties and luminescence mechanisms, linear relationships and detection limits, biocompatibility and water solubility, functionalization, and technical applications, particularly focusing on their applications in biosensing different bioactive ingredients along with some discussions on the challenges and perspectives in this promising field. This review can arouse research interest in the fabrication of biosensors by using CDs, including detection in major biomarkers, significant responses, and crucial enzymes in the pathological process, which will provide a vital tool and important bioinformatics for the early prevention, diagnosis, and treatment of diseases.